Characteristics of the Compassionate Use Program in Japan: An Analysis of Expanded Access Clinical Trials from 2016 to 2021. Issue 4 (7th June 2022) - Maeda, Hideki; Uchida, Marika; Kusano, Mikiko; Tsukamoto, Katsura; Yamanoi, Moeka
Abstract : Compassionate use is a system that provides patients with exceptional access to investigational new drugs to treat life‐threatening diseases that have no effective conventional treatments. The purpose of this study was to characterize and assess the current status of the compassionate use program's application in Japan by evaluating expanded access clinical trials (EACTs) conducted between 2016 and 2021. In this study, a data set containing all EACTs, and pivotal clinical trials (PCTs) conducted in Japan between February 2016 and April 2021 was obtained from the Pharmaceutical and Medical Devices Agency, systemically reviewed, and analyzed. During the 5 years since EACTs began in Japan, out of 2, 031 PCTs, 31 EACTs were conducted in Japan. Twenty‐four trials (77.4%) of the 31 EACTs used anticancer drugs and 5 of those trials (16.1%) were conducted in children. Furthermore, we conducted an EACT survey for drugs with a high degree of social and patient demands as recommended in the EACT notification. Among the 2, 031 PCTs, we found 152 trials with high degree of social and patient demands. Of these, EACT was implemented in 17 trials (11.2%). Days from the start of the EACT to the submission of new drug applications and the approval were 9.0 (67.0–56.5) and 208.0 (172.8–308.8) days, respectively. Of the 31 EACTs conducted, 24 (77.4%) drugs have been approved as of August 2021. This first comprehensive study on EACTs clarified the current status and issues of Japan's compassionate use system and the 5 years since the program initiated.